1964
DOI: 10.1055/s-0038-1654841
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sulfhydrylinhibitors and Glycine Derivatives on Fibrin Polymerization and the Physical Strength of Fibrin in Plasma

Abstract: SummaryThe influence of p-CMB, iodoacetamide, iodoacetic acid, N-ethylmaleimide, glycerinederivatives and of EDTA on thrombingeneration on fibrinpolymeriza- tion and on the physical strength of clots as expressed by spectrophotometrical and thrombelastographic measurements respectively has been examined.P-CMB and N-ethylmaleimide significantly inhibit the thrombin generation.EDTA retards the initial steps of the fibrinpolymerization and it increases the final turbidity. Its effect is neutralized by calcium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1969
1969
1977
1977

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…This has been previously shown by thromboelastograms of plasma clots from a patient congenitally deficient in Factor X I 1 1 (Beck, Duckert and Ernst, 1961). Gormsen and Silverntsen (1964) found the same thromboelastographic characteristics in plasma treated with various sulphydryl inhibitors. These authors did not demonstrate an effect on the urea solubility of clots with glycine-amide or glycine methyl ester.…”
Section: Discussionsupporting
confidence: 76%
“…This has been previously shown by thromboelastograms of plasma clots from a patient congenitally deficient in Factor X I 1 1 (Beck, Duckert and Ernst, 1961). Gormsen and Silverntsen (1964) found the same thromboelastographic characteristics in plasma treated with various sulphydryl inhibitors. These authors did not demonstrate an effect on the urea solubility of clots with glycine-amide or glycine methyl ester.…”
Section: Discussionsupporting
confidence: 76%
“…Quality criteria of urea treated fibrinogen: pH, ionic strength, and thrombin clottability (dilute thrombin solution, 10 NIH u/ml) were checked each time to be identical with a corresponding solution of untreated fibrinogen. Estimations of polymerization rate and degree were checked by random experiments (Gormsen & Sivertsen 1964). The urea concentration was always controlled after dialysis (urease method, Department of Clinical Chemistry, Sundby Hospital) and found to be from 0-3 x 10-4 moV1, concentrations which in the fibrin substrate of fibrin plates have no inhibitory effect on plasmin lysis.…”
Section: Methodsmentioning
confidence: 99%
“…Our data clearly indicate that in the presence of FSF, fibrin formed by ancrod is markedly more susceptible to plasmin degradation than fibrin formed by thrombin. This usually has been attributed solely to the fact that ancrod-formed fibrin is noncross-linked (24,29,47), since it has been shown that urea-soluble, noncross-linked clots are less resistant to lysis than crosslinked clots (48,49). In accord with these observations, results shown in Fig.…”
Section: Resultsmentioning
confidence: 99%